2022
DOI: 10.3389/fimmu.2022.934819
|View full text |Cite
|
Sign up to set email alerts
|

Prototheca bovis induces autophagy in bovine mammary epithelial cells via the HIF-1α and AMPKα/ULK1 pathway

Abstract: Prototheca bovis, a highly contagious pathogen, causes bovine mastitis, resulting in premature culling of affected cows and severe economic losses. Infection with P. bovis caused oxidative stress and apoptosis in bovine mammary epithelial cells (bMECs); however, mechanisms underlying P. bovis-induced autophagy remain unclear. Therefore, the autophagy flux induced by P. bovis in bMECs was analyzed by Western blot and laser scanning confocal microscopy. Expression levels of proteins in the HIF-1α and AMPKα/ULK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We identified autophagy as a crucial component of epithelial cell defense against mastitis pathogens, with the involvement of HIF-1α, AMPKα/ULK1 and the PTEN/PI3K-Akt-mTOR pathway [29][30][31]. Furthermore, we also reported that S. uberis infection induced autophagy by decreasing synthesis of pro-inflammatory cytokines [32].…”
Section: Introductionmentioning
confidence: 75%
“…We identified autophagy as a crucial component of epithelial cell defense against mastitis pathogens, with the involvement of HIF-1α, AMPKα/ULK1 and the PTEN/PI3K-Akt-mTOR pathway [29][30][31]. Furthermore, we also reported that S. uberis infection induced autophagy by decreasing synthesis of pro-inflammatory cytokines [32].…”
Section: Introductionmentioning
confidence: 75%
“…Both LAMP2 and RAB7 are lysosomeassociated proteins. 42 The expressions of Lamp2 and Rab7 were reduced in the aged HFD group, and RAB7 was reduced in the young HFD group, indicating that autophagy was inhibited by HFD, but increased Rab7 expression after APE intervention indicated the promotion of autophagy in the liver of aged mice in HAP. However, APE intervention did not affect the protein expression of RAB7.…”
Section: ■ Discussionmentioning
confidence: 91%
“…In this study, the upregulated expression of LAMP1 in aged mice supported the increased autophagic flux by APE intervention. Both LAMP2 and RAB7 are lysosome-associated proteins . The expressions of Lamp2 and Rab7 were reduced in the aged HFD group, and RAB7 was reduced in the young HFD group, indicating that autophagy was inhibited by HFD, but increased Rab7 expression after APE intervention indicated the promotion of autophagy in the liver of aged mice in HAP.…”
Section: Discussionmentioning
confidence: 94%
“…However, only a few of the compounds approached have been assessed in vivo and provided only a temporary resolution of clinical signs [37,40]. The refractoriness of Prototheca species to conventional treatment under in vivo conditions can be attributed to the development of pyogranulomatous reactions [46], high genetic diversity [40], and mechanisms of virulence and evasion of the immune re-sponse [47], such as biofilm production [23,24] and the induction of cellular apoptosis in mammary cells [48,49].…”
Section: Resultsmentioning
confidence: 99%